Asymmetric Catalytic Approach to Multilayer 3D Chirality. Issue 30 (6th May 2021) - Wu, Guanzhao; Liu, Yangxue; Rouh, Hossein; Ma, Liulei; Tang, Yao; Zhang, Sai; Zhou, Peng; Wang, Jia‐Ying; Jin, Shengzhou; Unruh, Daniel; Surowiec, Kazimierz; Ma, Yanzhang; et al.
Abstract: The first asymmetric catalytic approach to multilayer 3D chirality has been achieved by using Suzuki‐Miyaura cross‐couplings. New chiral catalysts were designed and screened under various catalytic systems that proved chiral amide‐phosphines to be more efficient ligands than other candidates. The multilayer 3D framework was unambiguously determined by X‐ray structural analysis showing a parallel pattern of three layers consisting of top, middle and bottom aromatic rings. The X‐ray structure of a catalyst complex, dichloride complex of Pd‐phosphine amide, was obtained revealing an interesting asymmetric environment nearby the Pd metal center. Three rings of multilayer 3D products can be readily changed by varying aromatic ring‐anchored starting materials. The resulting multilayer products displayed strong luminescence under UV irradiation and strong aggregation‐induced emission (AIE). In the future, this work would benefit not only the field of asymmetric synthesis but also materials science, in particular polarized organic electronics, optoelectronics and photovoltaics. Abstract : The first asymmetric catalytic approach to multilayer 3D chirality by using Suzuki‐Miyaura cross‐couplings in the presence of new chiral amide‐phosphines is reported. The resulting multilayer products showed strong luminescence under UV irradiation, and displayed strong aggregation‐induced emission (AIE).